2020
DOI: 10.5010/jpb.2020.47.1.100
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Screening and Antibacterial Activity Coix lacryma-jobi Oil

Abstract: Coix lacryma-jobi (Hanjeli) is known to posses anti-microbial properties. Therefore, phytochemical compounds of C. lacryma-jobi have been studied to produce novel antimicrobial agents as treatments against antibiotic-resistant bacteria.The objective of this study was to determine the phytochemical composition and antibacterial activity of the C. lacryma-jobi oil against Escherichia coli, Staphylococcus aureus, and Bacillus subtilis. The phytochemical composition of the oil was determined via gas chromatography… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
2
2

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 16 publications
(24 reference statements)
0
27
0
Order By: Relevance
“…Differences between groups were evaluated by one-way analysis of variance (ANOVA) followed by the Dunnet test to determine statistical significance. The significance level of this study was p <0.05 (Diningrat et al, 2020).…”
Section: Methodsmentioning
confidence: 78%
See 4 more Smart Citations
“…Differences between groups were evaluated by one-way analysis of variance (ANOVA) followed by the Dunnet test to determine statistical significance. The significance level of this study was p <0.05 (Diningrat et al, 2020).…”
Section: Methodsmentioning
confidence: 78%
“…In this study, the experimental results showed significant anti-diabetic and antioxidant activity of S. cumini leaves ethanol extract at concentrations of 200 & 400 mg/kg bw. This study has been able to explore the potential of S. cumini leaves ethanol extract for the treatment of diabetes and related complications such as oxidant stress to prove the traditional claim that Jamblang leaves can be used for the diabetes treatment (Diningrat et al, 2020;Panigrahy et al, 2017). This study shows that an increase in glucose levels was successfully controlled by S. cumini leaves ethanol extract, this is indicated by a decrease in glycosylated hemoglobin levels commonly used as a control indicator of diabetes where glycohemoglobin levels approach normal values in diabetics in metabolic control (Volpe et al, 2018;Zimmet et al, 2017).…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations